(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper empirically compares economic growth between the high, middle, and low-income countries from 1990 to 2021. The paper examines whether the growth patterns of countries before and after COVID-19 show any convergence or divergence of income. By employing descriptive analysis and panel data regressions an economic divergence in the time of the COVID-19 pandemic and ongoing global recession is detected. This paper prescribes an expansionary fiscal policy to contain the pandemic’s adverse effects and expand the aggregate demand at the global level, especially in middle and low-income countries.